Q: Factor: x2 – 121

A: This conversation has been flagged as incorrect. New answers have been added below ....

wedekind|Points 1182|

ASVNBKW88|Points 21|

Question

Asked 7/9/2012 2:59:17 PM

Updated 7/14/2014 8:20:59 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jerry06 [7/14/2014 8:20:59 PM]

Rating

3

x^2 - 121 = (x - 11)(x + 11)

Added 7/14/2014 8:20:57 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [7/16/2014 10:38:29 AM]

Multiply.
(8x4)(6x3)(-5x6)
**Weegy:** The answer is -12960 **User:** Multiply.
-9x4(5x - 2) **Weegy:** If 5x - 3 **User:** Multiply.
(9m + 10)2
**Weegy:** Can you kindly clarify your question please , is Multiply. (9m + 10) x 2 or
Multiply. (9m + 10)^2 ? (More)

Question

Expert Answered

Updated 6/8/2014 3:49:40 PM

3 Answers/Comments

(8x^4)(6x^3)(-5x^6) = -240x^13

Added 6/8/2014 3:48:01 PM

This answer has been confirmed as correct, not copied, and helpful.

-9x^4(5x - 2) = -45x^5 + 18x^4

Added 6/8/2014 3:48:41 PM

This answer has been confirmed as correct, not copied, and helpful.

(9m + 10)^2

= (9m + 10)(9m + 10)

= 81m^2 + 90m + 90m + 100

= 81m^2 + 180m + 100

= (9m + 10)(9m + 10)

= 81m^2 + 90m + 90m + 100

= 81m^2 + 180m + 100

Added 6/8/2014 3:49:40 PM

This answer has been confirmed as correct, not copied, and helpful.

Multiply.
(x + 2)(x - 4)
x represents something **Weegy:** Sequence of development would be the order in which the development happens and the rate of development is the speed at which development happens. The difference is important because speed does not necessarily have to do with the sequence. **User:** I dont understand that. can you multiply this? **Weegy:** Your question is not displayed in my screen may i know what you dont understand? **User:** what is (x+2) Multiplied by (x-4) **Weegy:** x=-4 **User:** Multiply
(9m + 10)*2
**Weegy:** 38m **User:** Multiply.
-9x4*(5x - 2)
**Weegy:** If 5x - 3 **User:** Multiply
(8x4)*(6x3)*(-5x6)
**Weegy:** The answer is -12960 **User:** Simplify
(63a)3
**Weegy:** Can you kindly clarify your question please , is it Simplify. (63a) x 3 or , Simplify. (63a)^3 ? **User:** its times 3 **Weegy:** = 6 **User:** Evaluate.
(-9)*0
**Weegy:** The answer is 1. Anything to the power of 0 will equal 1. Try it on your calculator. **User:** Subtract.
(3x3 + 2x5 - 1 + 7x4) - (5 + 9x4 + 9x5 - 5x3)
**Weegy:** 11x5 + 16x4 - 2x3 ? 6 **User:** Add.
(-5 + 6x7 + 2x5) + (9x7 + 5x5 + 9)
**Weegy:** 5x5= 25 **User:** Evaluate the polynomial.
x2 + 3y2 + 2xy, when x = 4 and y = 2 **Weegy:** Please clarify your question (More)

Question

Expert Answered

Updated 4/27/2014 10:50:06 PM

9 Answers/Comments

(63a)*3 = 189a

Added 4/27/2014 10:43:27 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [4/27/2014 10:46:09 PM]

(-9)*0 = 0

Added 4/27/2014 10:44:05 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [4/27/2014 10:46:10 PM]

(3x^3 + 2x^5 - 1 + 7x^4) - (5 + 9x^4 + 9x^5 - 5x^3)

= 3x^3 + 2x^5 - 1 + 7x^4 - 5 - 9x^4 - 9x^5 + 5x^3

= 8x^3 - 2x^4 - 7x^5 - 6

= 3x^3 + 2x^5 - 1 + 7x^4 - 5 - 9x^4 - 9x^5 + 5x^3

= 8x^3 - 2x^4 - 7x^5 - 6

Added 4/27/2014 10:45:57 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [4/27/2014 10:46:11 PM]

(-5 + 6x^7 + 2x^5) + (9x^7 + 5x^5 + 9)

= -5 + 6x^7 + 2x^5 + 9x^7 + 5x^5 + 9

= 4 + 15x^7 + 7x^5

= -5 + 6x^7 + 2x^5 + 9x^7 + 5x^5 + 9

= 4 + 15x^7 + 7x^5

Added 4/27/2014 10:47:31 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [4/27/2014 10:48:45 PM]

Add these together-this is an algebra problem
(-5 + 6x7 + 2x5) + (9x7 + 5x5 + 9) **Weegy:** (-5 + 6x7 + 2x5) + (9x7 + 5x5 + 9) =(-5+42+10) + (63+25+9) =47+97 =144 **User:** Evaluate the polynomial.
x2 + 3y2 + 2xy, when x = 4 and y = 2
**User:** Simplify:
-12y - 8x - 4x **Weegy:** -2xy is the answer (More)

Question

Expert Answered

Updated 6/8/2014 3:46:36 PM

3 Answers/Comments

(-5 + 6x^7 + 2x^5) + (9x^7 + 5x^5 + 9)

= 15x^7 + 7x^5 + 4

= 15x^7 + 7x^5 + 4

Added 6/8/2014 3:44:20 PM

This answer has been confirmed as correct, not copied, and helpful.

x^2 + 3y^2 + 2xy, when x = 4 and y = 2:

(4)^2 + 3(2)^2 + 2(4)(2)

= 16 + 3(4) + (8)(2)

= 16 + 12 + 16

= 44

(4)^2 + 3(2)^2 + 2(4)(2)

= 16 + 3(4) + (8)(2)

= 16 + 12 + 16

= 44

Added 6/8/2014 3:45:49 PM

This answer has been confirmed as correct, not copied, and helpful.

-12y - 8x - 4x = -12x - 12y

Added 6/8/2014 3:46:36 PM

This answer has been confirmed as correct, not copied, and helpful.

Multiply.
(-7x^4)(9x^3) **Weegy:** (-7x4)(9x3)=-756
(More)

Question

Expert Answered

Updated 8/6/2014 8:14:55 PM

1 Answer/Comment

(-7x^4)(9x^3) = -63x^7

Added 8/6/2014 8:14:55 PM

This answer has been confirmed as correct, not copied, and helpful.

27,401,560 questions answered

There are no comments.